Формування позитивного іміджу органів внутрішніх справ як суб’єкта забезпечення правопорядку в регіоні - Прокопенко, О. Ю.; Prokopenko, O. Y.; ORCID: http://orcid.org/0000-0001-5826-7830 (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 2 (69). - С. 166-174., 2015)
Досліджено етимологію терміна «імідж», проаналізовано наукові погляди вчених щодо формування позитивного іміджу органів внутрішніх справ. Сформульовано авторське бачення іміджу органів внутрішніх справ. Запропоновано шляхи підвищення іміджу органів внутрішніх справ як суб’єкта забезпечення правопорядку в регіоні.

The etymology of the term «image» is studied. It is stated that most scholars emphasize on the public aspect of the image. The author’s definition of «the image of internal affairs agencies as a subject of keeping law and order» is offered. Under this definition the author suggests to understand a set of social stereotypes that prevail in public opinions concerning the efficiency of realizing the measures to secure law and order in the region by the regional internal affairs agencies. It is established that the above mentioned category is one of the fundamental criteria of trust from people to the work of the police as subjects of keeping law and order in the region. Scientific points of view of scholars on the formation of positive image of the police are analyzed. Based on the analysis of the positions of lawyers and sociologists the author has proved his own vision of the list of key measures to create a positive image of the police as subjects of keeping law and order in the region. Among these measures the following are named and analyzed: a) constant work to create a positive image of the police within the information space with the active involvement of public and mass media; b) the active involvement of public into cooperation with internal affairs agencies in the field of keeping law and order and crime prevention; c) forming police officer’s personality as a professional worthy of the high rank title of a law enforcement officer; d) keeping the principle of transparency and openness in the police work as subjects of keeping law and order in the region; e) overcoming corruption component in the work of the police, including as subjects of keeping law and order in the region; f) implementing measures aimed at permanent psychological and moral, material encouragement of police officers, etc. Ways of improving the image of internal affairs agencies as subjects of keeping law and order in the region are offered.

Исследована этимология термина «имидж», проанализированы научные взгляды учёных по формированию положительного имиджа органов внутренних дел. Сформулировано авторское видение понятия имиджа органов внутренних дел. Предложены пути повышения имиджа органов внутренних дел как субъекта обеспечения правопорядка в регионе.
Prokopenko, O.Y. (2015), “Creating a positive image of the Interior as a subject of law and order in the region”, [“Formuvannia pozytyvnoho imidzhu orhaniv vnutrishnikh sprav yak subiekta zabezpechennia pravoporiadku v rehioni”], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 2, pp. 166-174.
Прокопенко, О. Ю. Формування позитивного іміджу органів внутрішніх справ як суб’єкта забезпечення правопорядку в регіоні // Вісник Харківського національного університету внутрішніх справ. - 2015. - № 2 (69). - С. 166-174.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; імідж; паблік рілейшенз; правопорядок; взаємодія з населенням; довіра населення; громадянське суспільство; Україна. Ukraine. Украина; image; public relations; Internal Affairs Agencies of Ukraine; law and order; public; interaction; trust; civil society; имидж; паблик рилейшнз; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; правопорядок; взаимодействие с населением; доверие населения; гражданское общество; Internal Affairs Agencies